Design of the Prototype Negative Ion Source for Neutral Beam Injector at ASIPP - 韦江龙 谢亚红 梁立振 顾玉明 邑伟 李军 胡纯栋 谢远来 蒋才超 陶玲 盛鹏 许永建 (Plasma science & technology, 2016)
In order to support the design, manufacture and commissioning of the negative- ion-based neutral beam injection （NBI） system for the Chinese Fusion Engineering Test Reactor （CFETR）, the Hefei utility negative ion test equipment with RF source （HUNTER） was proposed at ASIPP. A prototype negative ion source will be developed at first. The main bodies of plasma source and accelerator of the prototype negative ion source are similar to that of the ion source for EAST-NBI. But instead of the filament-arc driver, an RF driver is adopted for the prototype negative ion source to fulfill the requirement of long pulse operation. A cesium seeding system and a magnetic filter are added for enhancing the negative ion density near the plasma grid and minimizing co-extracted electrons. Besides, an ITER-like extraction system is applied inside the accelerator, where the negative ion beam is extracted and accelerated up to 50 kV.